Money illusion reconsidered in the light of cognitive science - János Vincze (Hungarian Academy of Sciences, Institute of Economics, 2017)
A basic principle of economics is that people always prefer a larger set of opportunities. Money illusion can be considered as the phenomenon that people may not perceive correctly their budget constraints, and may act in ways that run counter to this preference. In this view money illusion is a cognitive bias, worthwhile to overcome. Herein I argue that taking a view of human decision-making based on certain strands of cognitive psychology one can reinterpret the evidence for money illusion in two ways. First, I claim that money illusion is inescapable to some extent, and saying that we suffer from it is similar to alleging that we experience optical illusions, only because we are unable to see, say, individual atoms. Second, taking a view on "preferences" different from the traditional one, I contend that it may bring little benefit to get rid of money illusion even in the cases where it is possible to do so. To follow up the visual analogy, even if we can improve our eyesight it is not obviously desirable. These arguments seem to lead to a Candidean disposition: there is no possible improvement on the state of affairs as far as "money illusion" is concerned. Nonetheless, I will make some positive proposals concerning economic policy and economics research.
Keywords: D91; E40; B10; 330; money illusion; ecological rationality; knowledge representation